Living Hadis Dalam Tradisi Malam Kamis Majelis Shalawat Diba’ Bil-Mustofa - Adrika Fithrotul Aini (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
The research studies the tradition of Diba blessings in Mejelis bil Musthafa Yogyakarta. The focus is on knowing the signification of selawat in the community. It is based-field research, that is, concerning living-hadits phenomena characterized by descriptive, qualitative and inductive study. It means that the research aimed at gaining general picture or the description about living-hadits. The approach to be used in the study is a phenomenological one combined with functional theory. It results that the developing tradition in the life of Krapyak people is living-hadits one. In addition, there are some principal hadits to be used as guide in the activity. Besides, there is an important significance by the existence of the council, that is, spiritual aspect which cannot be lost from people tradition.